Effectiveness of triple fixed-dose combination in patients with inadequate blood pressure control - E. V. Zbyshevskaya; V. E. Gumerova; V. P. Erinchek; N. A. Logunova (Российский кардиологический журнал, 2022)
Aim. In routine clinical practice, to evaluate the antihypertensive efficacy, 24-hour blood pressure (BP) control, tolerability and effect on arterial stiffness of the triple fixed-dose combination (FDC) of amlodipine/indapamide/perindopril according to office and 24-hour ambulatory BP monitoring (ABPM) in patients with uncontrolled hypertension (HTN) using previous therapy.Material and methods. The study included 78 both sex outpatients over 18 years of age with essential HTN. The main inclusion criterion was HTN with inadequate BP control against the background of previous combination therapy including amlodipine, indapamide and perindopril as part of free- or fixed-dose combinations of antihypertensive drugs. All patients were prescribed triple FDC of amlodipine/ indapamide/perindopril (Triplixam) in accordance with the medication instruc tions. The patient’s condition was assessed during four follow-up visits: visit 1 — inclu- sion visit, visit 2 — after 4 weeks, visit 3 — after 12 weeks, visit 4 — after 24 weeks. At each visit, achievement of the target BP levels <140/90 mm Hg and <130/80 mm Hg was assessed, as well as the 24-hour BP profile. The dynamics of BP decrease, achievement of target BP values, 24-hour BP profile, and the effect of therapy on arterial stiffness according to ABPM were also assessed.Results. In the analyzed group of patients, the initial office BP was 160,8± 10,3/91,5±8,1 mm Hg. After 24 weeks, there was a significant BP decrease to 121,3±3,5/73,6±4,2 mm Hg (p<0,001). According to ABPM, an average daytime BP significantly (p<0,001) decreased from 153,9±9,04/8,38±9,18 to 120,3±4,7/73,4±4,7 mm Hg after 24 weeks of amlodipine/indapamide/perindopril FDC therapy. Similar patterns were also found for the average values of nighttime BP. Target BP <140/90 mm Hg after 4 weeks reached the majority (87,2%) of patients, and after 12 weeks, the proportion of pa tients who reached the target BP was 100%.Conclusion. In hypertensive patients with previous ineffective multiagent therapy, the triple FDC of amlodipine/indapamide/perindopril (Triplixam) provided high antihypertensive efficacy, good tolerability and adherence to therapy, and also demonstrated additional organ protection.